Dynamics of the parasite Marteilia refringens (Paramyxea) in Mytilus galloprovincialis and zooplankton populations in Alfacs Bay (Catalonia, Spain) - CARRASCO, N.; LÓPEZ-FLORES, I.; ALCARAZ, M.; FURONES, M. D.; BERTHE, F. C. J.; ARZUL, I. (Parasitology, 2007)
Since the first description of Marteilia refringens (Paramyxea) in flat oysters Ostrea edulis in 1968 in the Aber Wrach, Brittany (France), the life-cycle of this parasite has remained unknown. However, recent studies, conducted in the ‘claire’ system, have proposed the planktonic copepod Acartia grani as a potential intermediate host for the parasite. Nevertheless, experimental transmission of the parasite through the copepod has failed. Recent studies in this field have reported the presence of the parasite in zooplankton from the bays of the Delta de l'Ebre, a more complex and natural estuarine environment than that of the claire. As a result, 2 new Marteilia host species were proposed: the copepods Oithona sp. (Cyclopoida) and an indeterminate Harpaticoida. Consequently, the objective of the present work was to study the dynamics of Marteilia in the zooplankton community from one of the bays, Alfacs Bay, as well as the dynamics of the parasite in cultivated mussels during 1 complete year. Six different zooplankton taxa appeared to be parasitized by M. refringens, including copepods (3 Calanoida, Acartia discaudata, A. clausi and A. italica; 1 Cyclopoida, Oithona sp.; and 1 Harpacticoida, Euterpina acutifrons), and larval stages of decapod crustaceans (zoea larvae of Brachyura, probably Portumnus sp.). These taxa are thus proposed as new subjects for study, since they could be intermediate hosts in the infection process of mussels by Marteilia.